Utilization of Lifeskill Oriented Interactive Multimedia to Overcome the Negative Impacts of Gadget Use on Children in Probolinggo: Utilization of Lifeskill Oriented Interactive Multimedia to Overcome the Negative Impacts of Gadget Use on Children in Probolinggo - Ludfi Arya Wardana; Jauharotur Rihlah; Ahmad Izzuddin; Serlin Velinda; Tri Bagoes Pranoto Sanjoyo (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2023)
The purpose of this community service is to solve the problem of using gadgets in children by utilizing life skill-oriented interactive multimedia. The method used in this service is partner socialization, self-learning, mentoring, coaching, and act and do. The results of the service are at the socialization stage to teachers, students and parents of students. The partner self-learning stage is given learning videos about children, children's games, and the positive and negative impacts of gadgets, this is an incubation period. The partner mentoring stage follows mentoring material, namely life skills material, digital technology material, child development material. The coaching stage changes the mindset by integrating life skills material into classroom learning. The act and doing stage utilizes effective, interesting and in accordance with novelty methods, namely life skill-oriented interactive multimedia technology and a respectful gesture detection tool. The conclusion of this service is that partners can make positive use of gadgets by using lifeskill-oriented interactive multimedia and respectful gesture detection devices.